L`instrumentalisation de l`éthique dans la lutte antidopage en cyclisme sur route - Fincoeur, B. (Movement & Sport Sciences - Science & Motricité, 2016)
First defined as a public health problem from the 1960s, doping is rapidly condemned in the name of ethics. Bringing into opposition doping and ethics is however the result of a socio-cultural construct which did not always make sense to the cycling actors. After the numerous doping scandals from the end of the 1990s, the cycling world has been put under pressure by the economic constraints deriving from scandals. Sports ethics has therefore been invoked as a mean to ensure the survival of elite cycling. The emphasis on ethics is nevertheless purely opportunist as other types of unethical behaviors still develop without being discussed.